Multicomponent intervention provided by GPs to reduce cardiovascular risk factors: evaluation in an Italian large sample. (16th May 2021) - Colombo, Alessandra; Voglino, Gianluca; Lo Moro, Giuseppina; Taborelli, Stefano; Bianchi, Maria Antonietta; Gutierrez, Lucas Maria; Bert, Fabrizio; Della Rosa, Maria Cristina; Siliquini, Roberta
Abstract: Background: The cardiovascular risk increases in a multiplicative way when patients present more risk factors simultaneously. Moreover, the General Practitioners (GPs) play a crucial role in risk factors prevention and reduction. This work aimed to evaluate a multicomponent intervention in the Primary Care Department in an Italian Local Health Unit. Methods: A pre-post study was conducted in Northern Italy (2018). Patients were eligible if: aged between 30 and 60 years, not chronic patients, not affected by hypertension or hypercholesterolaemia. The GPs assessed body mass index, hypertension, abdominal obesity, low-density lipoprotein (LDL) values, glycaemic values, smoking and exercise habit (T0). A counselling by GPs to at-risk patients and a multicomponent health education intervention were performed. Reassessment occurred after at least 3 months (T1). Main analyses were chi-squared tests for gender differences, McNemar or marginal homogeneity tests for changes in paired data ( P  < 0.05 as significant). Results: Participants were 5828 at T0 (54.0% females) and 4953 at T1 (53.4% females). At T0, 99.1% presented at least one risk factor. Significant changes in paired data were reported for each risk factor. The greatest improvement frequencies occurred in glycaemia values (51.0%) and hypertension (45.6%), the lowest in abdominal obesity (3.7%). Some differences were recorded between genders, e.g. females reported higher improvement frequencies in hypertension ( P  = 0.001) and abdominal obesity ( P  < 0.001), whereas males in physical activity ( P  = 0.011) and LDL values ( P  = 0.032). Conclusion: The results showed significant changes for each risk factor, both for men and women. GPs and multicomponent educational interventions could play a key role in reducing cardiovascular risk factors.